Tapestry of postnatal emotional disorders: exploring the interplay of anxiety and depressive disorders and their associated risk factors in Sudanese women - Osman, Abdelgadir H.; Osman, Abdelaziz; Osman, Ibtihal A.; Hagar, Taisir (Frontiers in Public Health, 2024)
Background: This research aims to unravel the prevalence of postnatal emotional disorders with a focus on how postnatal anxiety remained under-estimated and often embroiled in postnatal depression.Methods: Out of 600 postnatal women invited to take part in this study from two prominent primary care clinics in Khartoum, 468 women agreed to participate in this study. Three questionnaires were utilized in this study, a Personal Information Questionnaire (PIQ), HADS (Hospital Anxiety and Depression Scale), and Beck depression Inventory (BDI). Multiple linear regression analysis applied to gauge risk factors with postnatal anxiety and depression.Results: More than half (52.50 %) of women showed evidence of both anxiety and depression using HADS, while only (20.9 %) of cases were detected by BDI, showing evidence of moderate depressive disorder. A substantial proportion (28.4%) showed high levels of comorbidity of anxiety and depression in the category of moderate to severe symptoms. Main risks factors for postnatal disorders were past psychiatric illness (β = 0.25, p = 0.001), a family history of psychiatric illness (β = 0.15, p = 0.002), and stress due to the number of children (β = 0.32, p = 0.001).This study advances our understanding of postnatal emotional disorders, particularly highlighting the prevalence as well as correlates of postpartum anxiety. More importantly, this study highlights the importance of routine screen for emotional distress in postnatal women.